Implementation of Deep Learning as Learning Activities in Elementary Education - Rita Buana Sari; Tri Widayatsih; Pahlawan Pahlawan (Journal of Social Work and Science Education, 2027)
This article examines the implementation of deep learning as learning activities at SD Negeri 15 Banyuasin I. The study was developed from a qualitative case study that explored how deep learning was understood, planned, implemented, evaluated, and followed up by teachers in daily classroom practice. Data were obtained through interviews, observation, and documentation involving the principal, teachers, and students. The findings indicate that the school has begun to implement deep learning through student-centered planning, contextual learning activities, collaborative discussion, problem-based tasks, reflection, formative assessment, and follow-up activities in the form of remedial support and enrichment. Teachers have attempted to design meaningful learning by considering students’ needs, interests, and abilities, although the quality of planning still varies among teachers. Classroom implementation has also moved toward active and contextual learning, yet several challenges remain, including uneven student readiness, limited learning resources, inconsistent documentation, and variations in teachers’ pedagogical competence. Evaluation practices have begun to include reflection, feedback, and analysis of learning outcomes, but a more systematic documentation system is still needed to strengthen data-based decisions. The article concludes that deep learning at SD Negeri 15 Banyuasin I has been implemented as a developing learning culture rather than as a fully established model. Strengthening teacher capacity, collaborative planning, authentic assessment, and continuous follow-up is necessary to make deep learning more consistent, meaningful, and sustainable in elementary education.